Investigating the Adoption of Virtual Libraries by Police Academies in Indonesia: An Enhanced TAM Model Aligned with the SDGs - Rubiyo, Rubiyo; Fakhruddin, Fakhruddin; Yulianto, Arief; Widada, Tri (Journal of Ecohumanism, 2024)
The evolution of digital technology has changed the educational landscape, with virtual libraries becoming essential in the modern learning environment. The study investigates the adoption of virtual libraries among Indonesian police academies, where cadets need access to resources that support theoretical and practical training needs. This study aims to evaluate the relationship between perception of ease of use (PEOU), perception of usability (PU), external aspiration (EA), and alignment with Sustainable Development Goals (SDG) 4 in shaping cadets’ intentions to use virtual libraries. Using an enhanced Technology Acceptance Model (TAM) framework, this quantitative study analyzed data from 140 cadets through structural equation modeling to examine the direct and indirect pathways of adoption intent. The findings revealed that PU significantly influenced adoption intentions, while PEOUs played a smaller role, suggesting that cadets prioritized the practical benefits of virtual libraries. However, neither the PU nor the PEOU mediates the relationship between EA, SDG alignment, and adoption intent, which suggests that external aspirations and SDG alignment alone are not enough to encourage cadet adoption in the absence of perceived direct benefits. These findings highlight the complex nature of technology adoption in special education settings, which emphasizes the need for tailored resources aligned with the cadet’s operational and academic goals. The study contributes to the TAM literature by combining sustainability and aspiration dimensions, which offers insights for academy administrators and policymakers to improve the relevance of virtual libraries. To encourage adoption, the study recommends designing content that addresses cadet-specific training needs. Future research may explore the role of institutional support and longitudinal assessments to capture evolving perceptions of virtual libraries, further informing sustainable practices in police training.